Application and Development Trend of 5G Communication Technology in Microelectronics - Zhang, Ruolei (International Journal of Computer Science and Information Technology, 2024)
This study delves into the synergistic relationship between 5G communication technology and microelectronics, and how it shapes the future of the scientific and technological landscape. Through a comprehensive blend of theoretical analysis and empirical research, we examine how 5G technology propels the advancement of microelectronics, and vice versa. Our findings reveal a symbiotic relationship between the two, driving the overall progress of the electronic information industry. The distinctive features of 5G technology—high speed, minimal delay, and extensive connectivity—demand that microelectronic chips exhibit superior processing capabilities and energy efficiency. This, in turn, fuels the relentless innovation in microelectronics. Simultaneously, advancements in microelectronics bolster the performance and cost-effectiveness of 5G equipment, facilitating its widespread adoption. Furthermore, this paper explores the convergent trends in 5G communication and microelectronics, along with the challenges and strategies for their integrated growth. It offers insights into potential avenues for innovation and development in these intertwined domains.